Website Babies Portal: development and evaluation of the contents regarding orofacial functions (Journal of Applied Oral Science, 2013)
Education mediated by technology facilitates the access to information and can reach more people, including a broader range of socio-economic groups and ages, and at a low-cost. The website "Babies Portal - Speech-Language Pathology/Audiology and Dentistry" (http://portaldosbebes.fob.usp.br) was developed to provide parents with information on communication procedure disorders and oral health, enabling them to prevent and identify any changes in development early while looking for the best treatment. Objective: The objective is to describe the development and evaluation of the content pertaining to the oral functions featured in the "Babies Portal". Methods: The first stage consisted of a literature review, development/selection of illustrations and an evaluation of the possible external links that could be available. In the second stage, 10 speech-language and hearing pathologists (group A) and five parents of babies (group B) evaluated the website via an online form, which included ethical and personal information and questions about the quality, technical information and comparative prior knowledge acquired after the access. In the first stage, there was the construction of five sections ("The Oral Functions", "Breastfeeding", "Food", "Pacifier, baby bottle and finger sucking" and "Breath") based on scientific studies, presenting objective information, content links prepared by the Ministry of Health and a Dentistry section in the "Babies Portal" website. Videos, static and dynamic images were also distributed throughout the sections. Results: Regarding the second stage, 90% of all speech-language and hearing pathologists judged a good/excellent quality for all sections and classified the technical quality as very good. By their turn, 88% of the parents (group B) reported that the website helped or helped very much in understanding the contents, and 80% rated the quality as good or excellent. Conclusions: Five sections concerning the oral functions were structured, and the results collected from groups A and B suggest that the content provided is adequate and reliable.